(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper explores Consumer behaviours function is to research the collection, purchase or use of ideas, goods and services to meet their requirements or desires by individual clients, groups or organizations. This applies to the behavior and underlying intentions of customers in the industry. The marketing manager’s understanding of consumer behavior allows him to recognize consumer needs and wishes in the market. The customer follows a decision-making process characterized by identification of issues, alternative evaluation, decision about buying, decision after purchasing. The consumer behavior analysis suggests that consumers are business actors. The position theory approach suggests that consumers play different roles on the market. Consumers perform these positions in the decision making process, beginning with the data provider, from the customer to the payer and the disposer. The paper discusses cultural factors, methods, social factors and phases in marketing consumer behaviour.